Eco-sustainable passive treatment for mine waters: Full-scale and long-term demonstration. (15th February 2021) - Orden, Salud; Macías, Francisco; Cánovas, Carlos R.; Nieto, José Miguel; Pérez-López, Rafael; Ayora, Carlos
Abstract: This paper tries to analyse the technical and economic performance of a full-scale passive Disperse Alkaline Substrate (DAS) treatment plant steadily operating for 28 months (840 days) to treat extremely acidic and metal rich mine waters in the Iberian Pyrite Belt (SW Spain). For the first time, an economic evaluation of this technology and its comparison with other passive treatments is reported. During this period, around 56, 000 m 3 of mine waters have been treated, without significant clogging or exhaustion of the alkaline substrate. The efficiency of the system is demonstrated by a significant decrease in the average net acidity (from 2005 to −43 mg/L as CaCO3 equivalent) and the total elimination of Al, Cu, REY, Zn, As, Cr, Mo, V, Cd, Pb, Co and other trace metals. Water quality of the treated output discharge meets the threshold values for irrigation and drinking standards, except for Fe, Mn and sulphate. The accumulation of elements of economic interest in the waste (e.g., 32 t of Fe, 6.1 t of Al, 0.8 t of Cu, 0.8 t of Zn, 39.4 kg of REE, 20 kg of Co or 1 kg of Sc), easily extractable with diluted acids, may turn a hazardous waste into a valuable resource. The benefits associated with the revalorization of this metal-rich waste could reach a total of 27478 USD, but is more reliably estimated to be around 8243 USD due to technologic limitations. This benefit would help to defray the maintenance costs (8428 €) and make DAS an economically self-sustainable treatment. The annual treatment cost for DAS was 0.27 €/m 3, being the lowest value found among other reported conventional passive schemes, and from 8 to 12 times lower compared to active technologies. The results obtained prove that the DAS technology is the most technically and economically sustainable way to decontaminate acid and metal-rich mine waters in abandoned mines. Graphical abstract: Image 1 Highlights: A long-term and eco-friendly treatment for highly polluted mine waters was tested. Removal of total acidity and most metals was achieved during 840 days. The technology showed an optimal cost-effectiveness (0.27 €/m3). Around 100 t of recoverable metals were retained in the tanks. DAS technology is a promising sustainable upcycling solution for AMD pollution.